Interconnection between several eye biomechanical and biometric parameters in children with axial and refractive mild myopia - Tsybulskaya, T. Ye.; Цибульська, Таміла Євгенівна; Цыбульская, Т. Е. (Запорізький державний медичний університет, 2016)
Aim – to study the relationship of biometric and biomechanical indicators of corneoscleral capsule of the eye in children with axial and refractive mild myopia. Materials and methods. Axial myopia was diagnosed in 32 children (64 eyes), refractive myopia – 18 (36 eyes). The control group – 16 children without ophthalmic diseases (32 eyes). Eye examination: visometry, automated refractometry, biomicroscopy, ophthalmoscopy, determination of the axial length of the eyeball and corneal hysteresis. Results. Significant differences were determined in the indicators of dioptric power of the cornea: 42.2 dpt in patients with axial and 44.7 dpt with refractive myopia (p<0.05), and also difference between patients with refractive myopia and the control group, in which the diopter power of cornea was 42.6 (p<0.05). There are also signifi cant differences in the indicators of the axial length of eyes between axial and refractive myopia – 24.5±0.64 mm and 23.1±0.43 mm (p<0.05). Significant difference with the control group in the axial length marked only in eyes with axial myopia 22.7±0.33 mm and 24.5±0.64 mm, respectively (p<0.05). Corneal hysteresis determined significantly reduced on eyes with both the axial and refractive myopia, which was significantly lower than in the indicators of emmetropic eyes of the control group 13.7 (p<0.05). Corneal hysteresis is inversely related to the axial length of the eyeball: in patients with axial myopia r -0.32, p<0.05; with refractive myopia r -0.36, p<0.05. Сorrelation between diopter power of cornea and axial length of the eyeball: r -0.53, р<0.05 in eyes with axial myopia and r -0.42, p<0.05 refractive myopia. Comparative analysis showed no significant differences between the corneal hysteresis, the axial length of the eye and the spherical component of myopia. Conclusions. In patients with axial and refractive mild myopia corneal hysteresis is reduced on average in 1.2 and 1.1 times, in comparison with emmetropic eyes. Corneal hysteresis is independent of spherical component of myopia, decreases with increasing of axial length of the eye in 82 % of cases with axial myopia and in 76 % of cases with refractive myopia. Мета роботи – вивчити взаємозв’язок біометричних і біомеханічних показників корнеосклеральної капсули ока в дітей з осьовою та рефракційною міопією слабкого ступеня. Матеріали та методи. Осьова міопія діагностована у 32 дітей (64 ока), рефракційна міопія – у 18 дітей (36 очей). Група контролю – 16 дітей без офтальмологічної патології (32 ока). Офтальмологічне обстеження: візометрія, авторефрактокератометрія, біомікроскопія, офтальмоскопія, визначення аксіальної довжини ока та кореального гістерезису. Результати. Вірогідні відмінності визначені в показниках діоптрійності рогівки: 42,2 діоптрії в пацієнтів з осьовою, 44,7 діоптрії з рефракційною міопією (р<0,05), а також між пацієнтами з рефракційною міопією та групою контролю: діоптрійність рогівки становила 42,6 діоптрії (р<0,05). Відзначили вірогідні відмінності в аксіальній довжині ока між осьовою та рефракційною міопією – 24,5±0,64 мм та 23,1±0,43 мм (р<0,05). Вірогідні відмінності з контрольною групою в аксіальній довжині відзначені тільки на очах з осьовою міопією 22,7±0,33 мм і 24,5±0,64 мм відповідно (р<0,05). Корнеальний гістерезис вірогідно знижений на очах з осьовою до 11,7 і з рефракційною міопією до 12,2, що є нижчим за показники еметропічних очей контрольної групи 13,7 (р<0,05). Корнеальний гістерезис має зворотну кореляцію з аксіальною довжиною ока: в пацієнтів з осьовою міопією – r -0,32, р<0,05; з рефракційною міопією – r -0,36, р <0,05. Кореляція між діоптрійністю рогівки та аксіальною довжиною ока: r -0,53 (р<0,05) на очах з осьової міопією та r -0,42 (р<0,05) на очах із рефракційною міопією. Порівняльний аналіз не показав відмінностей між кореальним гістерезисом, аксіальною довжиною ока та сферичним компонентом міопії. Висновки. У пацієнтів з осьовою та рефракційною міопією слабкого ступеня кореальний гістерезис знижений у середньому в 1,2 та 1,1 раза порівняно з еметропічними очима. Корнеальний гістерезис не залежить від сферичного компонента короткозорості, знижується зі збільшенням аксіальної довжини ока у 82 % випадків при осьовій та в 76 % випадків при рефракційній міопії. Цель работы – изучить взаимосвязь биометрических и биомеханических показателей корнеосклеральной капсулы глаза у детей с осевой и рефракционной миопией слабой степени. Материалы и методы. Осевая миопия диагностирована у 32 детей (64 глаза), рефракционная миопия – у 18 (36 глаз). Группу контроля составили 16 детей без офтальмологической патологии (32 глаза). Офтальмологическое обследование: визометрия, авторефрактокератометрия, биомикроскопия, офтальмоскопия, определение аксиальной длины глаза и корнеального гистерезиса. Результаты. Достоверные различия определяются в показателях диоптрийности роговицы: 42,2 диоптрии у пациентов с осевой и 44,7 диоптрии с рефракционной миопией (р<0,05), а также между пациентами с рефракционной миопией и группой контроля, в которой диоптрийность роговицы составила 42,6 диоптрии (р<0,05). Отмечаются достоверные различия в аксиальной длине глаза между осевой и рефракционной миопией – 24,5±0,64 мм и 23,1±0,43 мм (р<0,05). Достоверные различия с контрольной группой в аксиальной длине отмечены только на глазах с осевой миопией 22,7±0,33 мм и 24,5±0,64 мм соответственно (р<0,05). Корнеальный гистерезис достоверно снижен на глазах с осевой до 11,5 и с рефракционной миопией 12,2, что ниже показателей эмметропических глаз контрольной группы 13,7 (р<0,05). Корнеальный гистерезис имеет обратную корреляцию от аксиальной длины глаза: у пациентов с осевой миопией – r -0,32, р<0,05; с рефракционной миопией – r -0,36, р<0,05. Корреляция между диоптрийностью роговицы и акси- альной длиной глаза: r -0,53, р<0,05 на глазах с осевой миопией и r -0,42, р<0,05 на глазах с рефракционной миопией. Сравнительный анализ не показал различий между корнеальным гистерезисом, аксиальной длиной глаза и сферическим компонентом миопии. Выводы. У пациентов с осевой и рефракционной миопией слабой степени корнеальный гистерезис снижен в среднем в 1,2 и 1,1 раза в сравнении с эмметропическими глазами. Корнеальный гистерезис не зависит от сферического компонента близорукости, снижается с увеличением аксиальной длины глаза в 82 % случаев при осевой и в 76 % случаев при рефракционной миопии.
Взаємозв’язок деяких біомеханічних і біометричних показників ока в дітей з осьовою та рефракційною міопією слабкого ступеня
Взаимосвязь некоторых биомеханических и биометрических показателей глаза у детей с осевой и рефракционной миопией слабой степени
Keywords: Diagnostics; Children; Myopia; Діагностика; діти; міопія; диагностика; дети; миопия